The Authority To Resolve Disputes For The Election Of Village Head In The Indonesian Area - Rosidi, Ahmad; Nurcahyo, Edy (CV. Inara, 2021)
The Village Head Dispute Resolution Mechanism should be regulated in detail and clearly in the norms that apply as law, which should also contain provisions regarding the Village Head dispute resolution mechanism, because these provisions are very important, where each region is required to make a Regional Regulation, related to the issue of the settlement of the village head election, which regulates the election of the village head, including providing arrangements for the settlement of village head election disputes. The Regional Regulation is the juridical basis used by the Head of government at the regional level, namely the Regent and Deputy Regent. This research is a nomative law research in which the approach used is the library or statutory approach through a study of the decisions on the results of the dispute over the village picades. The technique of collecting legal materials is carried out by means of library research. The analysis of legal materials is carried out in a qualitative deductive manner so that a conclusion can be drawn according to the needs of what has been studied. What has been researched is the regent's responsibility as a regional head which is carried out in accordance with the Regional Regulation to form an Election Committee, a Sub-District Supervisory Committee, a District Research Committee, and a Dispute Resolution Team formed directly by the East Lombok Regent. The pattern of village head election dispute resolution carried out by the local government is through deliberation with the roles of negotiator, mediator and conciliator.